2008
DOI: 10.1182/blood-2008-02-140665
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib crosses the blood-brain barrier and is an efficient therapy for central nervous system Philadelphia chromosome–positive leukemia

Abstract: Although imatinib, a BCR-ABL tyrosine kinase inhibitor, is used to treat acute Philadelphia chromosome-positive (Ph ؉ ) leukemia, it does not prevent central nervous system (CNS) relapses resulting from poor drug penetration through the blood-brain barrier. Imatinib and dasatinib (a dual-specific SRC/BCR-ABL kinase inhibitor) were compared in a preclinical mouse model of intracranial Ph ؉ leukemia. Clinical dasatinib treatment in patients with CNS Ph ؉ leukemia was assessed. In preclinical studies, dasatinib i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
243
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(268 citation statements)
references
References 33 publications
12
243
0
6
Order By: Relevance
“…This is likely to represent a significant clinical problem as the brain is a frequent site of relapse in melanoma. However, secondgeneration tyrosine kinase inhibitors such as dasatinib have shown some promise in Philadelphia chromosome-positive leukaemia patients with CNS involvement (Porkka et al, 2008). Furthermore, studies have looked at modulating the distribution of drugs such as imatinib by targeting P-glycoprotein and other drug protein transporters (Breedveld et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to represent a significant clinical problem as the brain is a frequent site of relapse in melanoma. However, secondgeneration tyrosine kinase inhibitors such as dasatinib have shown some promise in Philadelphia chromosome-positive leukaemia patients with CNS involvement (Porkka et al, 2008). Furthermore, studies have looked at modulating the distribution of drugs such as imatinib by targeting P-glycoprotein and other drug protein transporters (Breedveld et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, dasatinib could also reach sanctuary areas like cerebrospinal fluids, which has not been found by other TKIs. 41,42 The response to TKI is the most important prognostic factor and it is the basis of continuing or changing the treatment. The responses are defined as "optimal," "failure" or "warning."…”
Section: Discussionmentioning
confidence: 99%
“…51 Finally, Porkka et al reported that dasatinib is capable of increasing survival in a K562 intracranial chronic myeloid leukemia (CML) mouse model, whereas imatinib is not. 52 Overall, these results indicate that a more active CNS prophylaxis must be administered when using imatinib as front-line therapy.…”
mentioning
confidence: 99%